2018
DOI: 10.3892/mco.2018.1549
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress response induced by chemotherapy in leukemia treatment (Review)

Abstract: Oxidative stress (OS) has been linked to the etiology and development of leukemia as reactive oxygen species (ROS) and free radicals have been implicated in leukemogenesis. OS has beneficial and deleterious effects in the pathogenesis and progression of leukemia. High-dose chemotherapy, which is frequently used in leukemia treatment, is often accompanied by ROS-induced cytotoxicity. Thus, the utilization of chemotherapy in combination with antioxidants may attenuate leukemia progression, particularly for cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(45 citation statements)
references
References 82 publications
3
37
0
5
Order By: Relevance
“…Also, other examinations showed that both drugs induce lipid peroxidation and decrease GSH in isolated neurons. Our results are consistent with previously published data examining Ara-C, and IFOS-induced oxidative stress in several systems [29,30].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Also, other examinations showed that both drugs induce lipid peroxidation and decrease GSH in isolated neurons. Our results are consistent with previously published data examining Ara-C, and IFOS-induced oxidative stress in several systems [29,30].…”
Section: Discussionsupporting
confidence: 93%
“…Our measured toxicity parameters showed that Ara-C, and IFOS significantly induce ROS formation. Previous studies showed that Ara-C, and IFOS increase the ROS formation and oxidative stress in normal and tumor cells [29,30]. Also, other examinations showed that both drugs induce lipid peroxidation and decrease GSH in isolated neurons.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Установлено, что универсальным механизмом действия цитостатической терапии является индукция окислительного стресса [12]. Повышенное образование свободных радикалов вносит существенный вклад в большинство побочных эффектов цитостатиков, а также в их генотоксическое действие на созревающие половые клетки.…”
Section: Introductionunclassified
“…The ions then act as free radicals and pick other ions from the surrounding normal cells causing oxidative stresses (OS) which leads to cell lysis and inflammation of the surrounding tissues (13). Literature has reported of necrosis causing leukemia as a result of OS development from chemotherapy (14). In contrast to necrosis, apoptosis (programmed cell death) occurs routinely in normal cells during growth and aging in homeostatic mechanism to retain cell population in tissues (15).…”
Section: Introductionmentioning
confidence: 99%